Digital Quran Application Features and User Satisfaction among Urban Muslims: Fitur Aplikasi Al-Qur’an Digital dan Kepuasan Pengguna Muslim Urban - Addiina Raihan Hamas; Arifuddin Tike; Haidir Fitra Siagian; Kamaluddin Tajibu; Muhammad Anshar Akil (Academia Open, 2026)
General Background: The expansion of internet access and mobile technology has encouraged the use of digital Qur’an applications to support religious practices among urban Muslims. Specific Background: Quranly provides interactive features such as reminders, progress tracking, and gamification designed to facilitate consistent Qur’an engagement. Knowledge Gap: Despite increasing adoption of digital Qur’an platforms, limited empirical research examines how application features relate to user satisfaction through trust mechanisms, particularly among urban Muslim users. Aims: This study analyzes the relationship between Quranly application features, user trust, and user satisfaction, including the mediating role of trust. Results: A quantitative survey of 140 active Quranly users analyzed using Structural Equation Modeling–Partial Least Squares shows that application features are positively associated with user satisfaction (β=0.266; p<0.05) and trust (β=0.452; p<0.05), while trust is also positively associated with satisfaction (β=0.346; p<0.05). Trust additionally functions as a complementary mediator between application features and satisfaction. Novelty: The study proposes an empirical mediation model linking digital Qur’an application features, trust, and satisfaction among urban Muslim users. Implications: The findings highlight the importance of feature reliability, content credibility, and service consistency in supporting trust and sustaining satisfaction in digital religious applications. Highlights • Interactive system attributes show significant relationships with satisfaction levels among Quranly users.• Trust functions as a mediating mechanism within digital religious platform usage.• Reliability and credibility of platform services support sustained user experience. Keywords Digital Quran Application; Application Features; User Trust; User Satisfaction; Urban Muslims